Interconnections, relationships, and environmental wholes: A phenomenological ecology of natural and built worlds - Seamon, David (Simon Silverman Phenomenology Center, Duquesne University Press, 2009)
In this article, I ask what the relationships, interconnections, and environmental wholes of ecology become in a phenomenological perspective. To answer this question, I consider one phenomenon from the natural world—color—and one phenomenon from the human-made world—vibrant urban places. To discuss a phenomenology of vibrant urban places, I turn to my own work on the bodily dimensions of environmental experience and action, especially as the lived body comes to know its everyday environment through the regularity and routine of extended time-space patterns contributing to the transformation of physical space into lived place. I also emphasize, after architectural theorist Bill Hillier, that the physical structure of place, particularly the spatial configuration of pathways, plays a major role in establishing whether streets are well used and animated or empty and lifeless. To discuss a phenomenology of color, I turn to the proto-phenomenology of Goethe, who devised a qualitative way of seeing and understanding that can rightly be called a phenomenology of the natural world. Most significantly for a phenomenological understanding of relationships, interconnections and environmental wholes, Goethe’s work demonstrates how light and color involve an underlying “belonging” seen in perceptual presence but only understood through a moment of insight in which all the parts are understood together and have a fitting place. This article was originally prepared as a keynote address delivered at the symposium, “Renew the Face of the Earth: Phenomenology and Ecology,” organized by the Simon Silverman Phenomenology Center at Duquesne University in Pittsburgh, Pa., March, 12, 2005.
Keywords: Phenomenology of place; Space syntax; Phenomenology and ecology; Goethean science; Goethe's theory of color; Place theory